Black Lightning. The fourth and final season [videorecording (DVD)] - Akil, Salim, 1964- (Warner Bros. Home Entertainment, 2021)
Jefferson Pierce, respected educator and father of two, is also Black Lightning, superpowered protector of Freeland. And he doesn't fight alone. He is joined by his superpowered daughters, Anissa, aka Thunder, and Jennifer, aka Lightning, as well as his ex-wife, metahuman expert Lynn. Together, the Pierce family combats the ills eroding their city, including a menacing gang that calls itself The 100 and infamous gangster Tobias Whale.